2023
DOI: 10.3389/fpsyg.2023.1241860
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality rehabilitation program on executive functions of children with specific learning disorders: a pilot study

Valentina Di Giusto,
Giulia Purpura,
Carla Fulvia Zorzi
et al.

Abstract: BackgroundThe application of Virtual Reality (VR) in the field of rehabilitation has been widely studied, because it has already proven to be an effective intervention for a variety of physical and cognitive conditions. Nevertheless, its application in pediatric rehabilitation is more recent. This pilot study aims to examine whether a VR-rehabilitation program may have positive effects on the Executive Functions (EFs) of children with Specific Learning Disorders (SLD).Materials and methodsTwenty-four children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, most of the mentioned reports in systematic reviews do not mention monitoring complications of this technology, as if it comes with pure benefit. [6,7,12,13] In this study, we identified a total of 4 controlled trials on skill development in autism, ADHD, and dyslexia; comprising a total of 208 patients, a sample size that does not match a very large population of interest. [8][9][10][11] Moreover, the age ranged in the four studies from 6-16 years, which means that VR technology is still not extensively available for early training of patients with learning difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most of the mentioned reports in systematic reviews do not mention monitoring complications of this technology, as if it comes with pure benefit. [6,7,12,13] In this study, we identified a total of 4 controlled trials on skill development in autism, ADHD, and dyslexia; comprising a total of 208 patients, a sample size that does not match a very large population of interest. [8][9][10][11] Moreover, the age ranged in the four studies from 6-16 years, which means that VR technology is still not extensively available for early training of patients with learning difficulties.…”
Section: Discussionmentioning
confidence: 99%